THE MEANING OF THE BEAUTIFUL BODY IN GRAHAM SWIFT’S FICTIONAL WORLD - Marginean, Alexandra Roxana (European Scientific Journal, ESJ, 2013)
As Bachelard, Lefebvre, Michel de Certeau, Bourdieu and others have contended, by the production of space and by relating to it in the world, the individual is constructing her/his identity. Spatial interaction builds who one is, and, if we consider the fact that the body is the closest “space” or circumscribed reality one has to symbolically produce, deal and come to terms with, the way people relate to their bodies may say a lot about their conception of self in the world, self image, and therefore identity and identity construction and presentation before the others. The body is also indispensable for inhabitation and dwelling in an environment. As the tool used to shape one’s surroundings, it is involved not only in the physical mapping of the world, but also in what has come to be called its symbolical, conceptual or “cognitive mapping” (Shields 2002: 265) which refers to how space reflects mentalities, practices and emotions. The interest in the body is all the more poignant against the background of twentieth-century events and consumerism, an aspect that is tackled in the introduction of the paper. This part also delineates the direction of this study, namely the manner in which Swift’s characters (ab)use their bodies in various ways, which is presented in the main part of our scrutiny. The approach is cultural studies. The conclusions draw on Arthur Frank’s work, the central idea being that the bodies we have analysed could be interpreted as plural and ambivalent.